2014
DOI: 10.1177/0269215514532478
|View full text |Cite
|
Sign up to set email alerts
|

Self-management interventions for chronic disease: a systematic scoping review

Abstract: Physiotherapists and occupational therapists make moderate contributions to self-management interventions. Most of these interventions are disease-specific and are most frequently based on the principles of behaviour change theories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(46 citation statements)
references
References 66 publications
2
42
1
1
Order By: Relevance
“…This finding differs from the previous review, which reported that many studies do not state clearly the theoretical model on which the self-management programme has been developed (Richardson et al 2014). …”
Section: Effectiveness In Improving Physical Activitycontrasting
confidence: 99%
“…This finding differs from the previous review, which reported that many studies do not state clearly the theoretical model on which the self-management programme has been developed (Richardson et al 2014). …”
Section: Effectiveness In Improving Physical Activitycontrasting
confidence: 99%
“…In health care systems, SM programs for patients with chronic conditions have become relevant fields of research, with 'expert patient' programs being implemented [5][6][7]. Already in 1997, the chronic care model was introduced by Wagner [8,9].…”
Section: Current Relevance Of Self-management In Health Carementioning
confidence: 99%
“…Yksilö voi toimia itseohjautuvasti mm. asettaessaan tavoitteita oman hyvinvointinsa edistämiseksi, suunnitellessaan omaa toimintaan sa, sekä tunnistaessaan haasteita ja esteitä mat kalla kohti asetettuja tavoitteita (4).…”
Section: Asiakkaan Ja Ammattilaisen Muuttuvat Roolitunclassified